Dietary patterns and lifestyle among Slovenian adolescents - Radivo, Manica (Obzornik zdravstvene nege, 2023)
Introduction: Healthy eating, physical activity and sleep are important determinants of the lifestyle of adolescents. The aim of this study is to investigate the relationship between adolescents' dietary patterns and their lifestyle, as well as to analyse the differences by gender and region of residence, and to establish associations between individual lifestyle patterns.Methods: The study was conducted in the spring of 2019 on a group of third-year students (n = 1,563) from randomly selected secondary schools in Slovenia. The average age of the participants was 18 years. Data were collected using an anonymous questionnaire created with the 1KA online tool, comprising 30 questions. Descriptive and inferential statistics were calculated using SPSS software. The t-test was used to determine statistically significant differences, while ?2statistic and Spearman's correlation coefficient were used to determine statistically significant associations.Results: The study revealed a large deficit in the intake of vegetables, legumes and fish compared to the intake of fruit, as per recommendations, particularly in Eastern Slovenia. Statistically significant differences in nutritional status were identified between the two cohesion regions (U = 275.597, p = 0.003). A positive correlation was observed between the frequency of breakfast consumption during the week and the amount of sleep (rs = 0.177, p = 0.001), while a negative correlation was established between sedentary behaviour and regular physical activity among adolescents during their free time (rs = ?0.113, p = 0.001).Discussion and conclusion: The dietary habits of the adolescents participating in the study were not in line with the recommendations. Physical activity guidelines were also not followed by the adolescents. Future research should focus more on older adolescents (18 to 24 years) and examine the relationship between individual lifestyle factors.
Keywords: breakfast; fruits and vegetables; legumes; nutrition of adolescent; physical activity; prehrana dijakov; sadje in zelenjava; sleep; spanje; stročnice; telesna aktivnost; zajtrkovanje